Correlates of psychological care strategies for people with diabetes in the second Diabetes Attitudes, Wishes and Needs (DAWN2™) study. Issue 9 (31st March 2016) - Holt, R. I. G.; Nicolucci, A.; Kovacs Burns, K.; Lucisano, G.; Skovlund, S. E.; Forbes, A.; Kalra, S.; Menéndez Torre, E.; Munro, N.; Peyrot, M.
Abstract: Aims: To assess the ways in which healthcare professionals address psychological problems of adults with diabetes in the second Diabetes Attitudes, Wishes and Needs (DAWN2 ™ ) study. Methods: Approximately 120 primary care physicians, 80 diabetes specialists and 80 nurses and dietitians providing diabetes care participated in each of 17 countries ( N =4785). Multiple regression analyses were used to evaluate independent statistically significant associations of respondent attributes concerning psychological care strategies, including assessment of diabetes impact on the patient's life, assessment of depression, provision of psychological assessment and support, and coordination with mental health professionals. Results: Psychological care strategies were positively associated with each other but differed by healthcare practice site and discipline; nurses and dietitians were less likely to assess depression than other healthcare professionals, while primary care physicians were less likely to coordinate with mental health specialists or ask patients how diabetes affects their lives. Psychological care was positively associated with healthcare professionals' beliefs that patients need help dealing with emotional issues and that clinical success depends on doing so, and also with level of psychological care training, multidisciplinary team membership and availability of resources for psychological care. There were significant between‐country variations in psychological care strategies, before and after adjustment for individual‐level factors, and significant country‐by‐covariate interactions for almost all individual‐level factors investigated. Conclusions: Improvements in training and resources, recognition and assessment of psychological problems, and increased belief in the efficacy of psychological support may enhance healthcare professionals' efforts to address psychological problems in adults with diabetes. What's new?: This study examined barriers and facilitators for healthcare professionals in the provision of person‐centred psychological care and self‐management support for people with diabetes. Psychological care was positively associated with beliefs that patients need help with emotional issues and that clinical success depends on doing so. There were differences in psychological care between disciplines and countries. The provision of psychological care improved with training received and desired, multidisciplinary team membership, and resources for psychological care.